Menelisik Fenomena Online Buzz pada IPO Saham Teknologi - Widhi Nugraha Wardana; Gede Sri Darma (J-MAS (Jurnal Manajemen dan Sains), 2022)
In recent years, the initial public offerings of technology companies on the Indonesia Stock Exchange have drawn great interest of investors. However, difficulties arise in assessing the valuation of a relatively new company, hence retail investors may turn to other fundamental factors such as sales growth and issuing size with online media become a source of information and forum for discussions. These online activities are increasing ahead of the IPO, causing a high online buzz phenomenon. This study aims to examine the effect of sales growth, issuing size and online buzz on technology stock underpricing. Using path analysis techniques on a sample of 23 technology stocks that conducted IPOs between 2000 – 2022, this research found that higher issuing size will generate higher online buzz. However, this study unable to find evidence of significant relationship between sales growth on online buzz, online buzz on underpricing and issuing size on underpricing. The limited sample in this study can be used as a consideration for further research opportunities on IPO in other sectors with larger population. It is also interesting to conduct both quantitative and qualitative study on online buzz in various market conditions to enrich the literature on company IPOs.